Stakeholder Collaboration in Tourism Village Branding: The Case of Gombengsari - Yuslinda Dwi Handini; Abul Haris Suryo Negoro; Adhiningasih Prabhawati; Jaymei Yoseka; Ari Ahmad Tamami; Muhammad Nurul Muflikhin (Centre of Excellence in Tourism Udayana University, 2025)
This study argues that cross-stakeholder co-creation, which aligns internal and external branding capabilities, is most effective in converting local assets into a coherent place brand; however, it is still limited by formalistic participation and institutional disharmony. Tourism village branding in Indonesia generally emphasizes promotion without integrating branding capabilities and co-creation, especially in the context of tourism villages. Therefore, we examined Gombengsari (Banyuwangi), which is based on coffee and Etawa goats, as a representative case. The research objective is to develop an integrated, co-creation-based lens to explain how assets are mobilized through the branding process to achieve economic outcomes and destination identity. Using a descriptive qualitative approach, data were collected through observation, documentation, interviews, and focus group discussions (FGDs) with the government and community (purposive–snowball sampling), coded in NVivo, and analyzed interactively. The findings reveal three key assets, including natural, institutional, and social, driven by top-down (tiered policies) and bottom-up (community participation and the slogan “Come–Feel–Enjoy–Stay”) processes. Two brief pieces of evidence: (1) the budget of the Tourism Awareness Group (Pokdarwis) of around Rp200 million/year limits funding for events and promotions; (2) a farm with ±200 Etawa goats produces ±300–500 liters/week, which has been successfully packaged as an educational experience. This article presents a co-creation ecosystem framework that integrates branding capabilities (both internal/external) and co-creation to enhance place branding and local economic benefits. Its limitations are its single case study and short temporal horizon, opening up space for comparative studies across destinations.